Recognition of the Skills and Knowledge of Iranian Auditors at workplace - Nahid Sadat Khalife Soltani; Farzaneh Nassirzadeh (Iranian Journal of Accounting, Auditing & Finance, 2018)
The purpose of this research is to investigate and identify the skills, knowledge, and attitudes required by today's auditors in Iran. To this end, a questionnaire was distributed among the auditors of audit firms located in Mashhad to determine the significance of the skills identified for the efficiency of auditors and the performance of auditors in each of the skills. For data analysis, the exploratory factor analysis and the T test student were used. The results show that the most important skills required from the auditors' point of view are accounting and auditing practices, mastery of accounting and auditing standards and regulations, and honesty. The 37 of the examined skills were categorized into 6 groups, which were titled as the communication and decision-making competency, technical and functionality competency, planning and future planning competency, organizational perception competency, subjective competency, and professional competency. The greatest gap is between the performance and the importance of planning and foresight competency and the shortest gap is between performance and the importance related to the competence of organizational perception. Moreover, the results indicate that auditors have a good performance in complying with legal requirements and paying attention to ethical values ​​and ethics. The findings show the need for review in the areas of accounting and auditing to improve the auditor's competencies through adding courses entitled, communication’s skills of the vocabulary, audio and writing in the course syllabus, and using the apprenticeship course at different levels of education.